2011
DOI: 10.1093/rpd/ncr268
|View full text |Cite
|
Sign up to set email alerts
|

Status of radiation protection in interventional cardiology in four East European countries

Abstract: Level of staff and patient radiation protection in interventional cardiology in four counties (Bosnia and Herzegovina, Croatia, Montenegro and Serbia) as a part of International Atomic Energy Agency project (RER/9/093) are presented. Patient doses were assessed in terms of air kerma area product (KAP), peak skin dose (PSD) or air kerma at interventional reference point (K(IRP)). Results were available from nine hospitals: 775 patients for KAP, 157 for PSD and 437 for K(IRP). Eight centres reported KAP >100 Gy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, these surveys have not had the wide scope of the present investigation. They have been either limited to certain geographical regions (Borrás 1997, Fleitas et al 2006, Ciraj-Bjelac et al 2011, to specific modalities (Borrás et al 2003, Vassileva et al 2012, Muhogora et al 2008, 2010, Tsapaki et al 2009 or their purpose was to obtain a snapshot of practices in a few selected areas (IAEA 1995(IAEA , 2004(IAEA , 2005(IAEA , 2010. Several of the IAEA studies concluded that there was considerable scope for improvement in the implementation of optimisation (Muhogora et al 2010, Ciraj-Bjelac et al 2011, Vassileva et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…However, these surveys have not had the wide scope of the present investigation. They have been either limited to certain geographical regions (Borrás 1997, Fleitas et al 2006, Ciraj-Bjelac et al 2011, to specific modalities (Borrás et al 2003, Vassileva et al 2012, Muhogora et al 2008, 2010, Tsapaki et al 2009 or their purpose was to obtain a snapshot of practices in a few selected areas (IAEA 1995(IAEA , 2004(IAEA , 2005(IAEA , 2010. Several of the IAEA studies concluded that there was considerable scope for improvement in the implementation of optimisation (Muhogora et al 2010, Ciraj-Bjelac et al 2011, Vassileva et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…The placement and quantity of personal dosimeters worn while using a shielding apron varies by country. In the United Kingdom and Eastern Europe, the dosimeter is recommended to be worn under the apron [10,11]. This practice is in line with the International Commission on Radiological Protection's recommendations, which state that a single dosimeter worn under a lead apron can provide a reasonable estimate of the effective dose [12] and measure the dose to which protected organs are exposed [10].…”
Section: Jrprmentioning
confidence: 91%
“…Projects include, among others, training, assessment of the radiation safety situation in each country or region as well as dissemination of information and provision of support to improve the existing situations. [2][3][4][5][6][7][8][9][10] Another method that has been utilized is providing support through publication of guidance and safety reports. One would suppose that, since regulations and guidance documents have been published for so long, their contribution to enhancing radiation safety would be undisputed and by now it would have been quantitatively known how much radiation protection has benefited due to regulations.…”
Section: Introductionmentioning
confidence: 99%